Vibration-induced white finger and cold response of digital arterial vessels in occupational groups with various patterns of exposure to hand-transmitted vibration - Bovenzi, Massimo (Scandinavian Journal of Work, Environment & Health, 1998)
' ' OBJECTIVES ': 'This study investigated the relation between vibration exposure, the prevalence of white fingers, and the cold response of digital arterial vessels in workers using vibrating tools.' ' METHODS ': 'The change in finger systolic blood pressure (FSBP) at 15 and 10°C as the percentage of the pressure at 30°C (FSBP%) was measured in 455 healthy referents and 822 workers exposed to hand-transmitted vibration. Vibration measurements were performed on a representative sample of the hand-held tools, and exposure to hand-transmitted vibration was assessed in terms of 8-hour energy-equivalent frequency-weighted acceleration [A(8)] and total operating time with vibrating tools.' ' RESULTS ': 'The prevalence of white fingers was 1.1% for the referents and ranged from 9.0% to 51.6% for the vibration-exposed groups. The estimated mean value of A(8) was 8.3 m/s2 for the quarry drillers, ranged between 2.8 and 4.7 m/s2 for the construction workers, caulkers, foundry workers and forestry workers, and was
Keywords: cold provocation test; exposure-response relationship; finger systolic blood pressure; predictive value; sensitivity; specificity; vibrating tool